2020
DOI: 10.1051/mbcb/2020043
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular tori interfering with the mobility of the lingual frenulum: a short case report

Abstract: Introduction: Tori are benign hamartoma-like bone excrescences, usually asymptomatic. Their removal should not be systematic. Observation: A 62-year-old patient showed bilateral tori only leaving a 1.5 mm space for the lingual frenulum path between them. The direct functional consequence was a frequent blockage of the salivary caruncles below the tori. Tori resection was performed under local anaesthesia. Surgical outcome was simple with conventional analgesic treatment and oral care. Comfort and function were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…(Springer, 1954) Since then, there were only two cases relating the interference of the tongue movement and its structures by mandibular tori. (Casenave et al, 2021;Shimahara et al, 2007) Both cases did not report which speech impairment complaint the patient had. In the present case, the patient reported difficulties to pronounce words containing the letters R, L, T, D, Z, S and N. Thus, multidisciplinary evaluation is needed for a better treatment of choice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Springer, 1954) Since then, there were only two cases relating the interference of the tongue movement and its structures by mandibular tori. (Casenave et al, 2021;Shimahara et al, 2007) Both cases did not report which speech impairment complaint the patient had. In the present case, the patient reported difficulties to pronounce words containing the letters R, L, T, D, Z, S and N. Thus, multidisciplinary evaluation is needed for a better treatment of choice.…”
Section: Discussionmentioning
confidence: 99%
“…(Faria et al, 2019;Suzart & Carvalho, 2016;Walsh & McKenna Benoit, 2019) Given the lesion features of the case presented, greater the size of the lesion, the greater the chance of harming the positioning of the tongue and the lingual frenulum. (Auškalnis et al, 2015;Casenave et al, 2021;Mourão et al, 2019;Springer, 1954) The frenulum fold the floor of the mouth and the tongue, the lingual praxis depends on its complete function. When there is something preventing its complete functioning, problems arise in the articulatory movements of the tongue and, consequently, speech problems interfere with the quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in recent years, several reports have advocated that OPTPs may not deliver all anticipated effects and could be harmful. The pros and cons of using OPTPs remain to be debated [ 2 , 4 , 5 ]. During general anesthesia, a comparative study between a group using OPTPs and a group abstaining from OPTPs reported a higher incidence and severity of sore throat in the group using OPTPs, although there are probably differences due to OPTPs insertion time and insertion method [ 2 , 9 ].…”
Section: Discussionmentioning
confidence: 99%